Dijkstra algorithm-based ray tracing for tunnel-like structures. (3rd December 2019) - Uchida, Kazunori; Barolli, Leonard
This paper deals with ray tracing in a closed space such as tunnel or underground by using a newly developed simulation method based on the Dijkstra Algorithm (DA). The essence of this method is to modify the proximity-node matrix obtained by DA in terms of three procedures, path-selection, path-linearisation and Line-Of-Sight (LOS) check. The proposed method can be applied to ray tracing in complicated structures ranging from an open space such as Random Rough Surface (RRS) or urban area to a closed space such as tunnel or underground. In case of a closed space, however, more detailed discussions are required than in case of an open space, since especially at a grazing angle of incidence, we have to take account of the effects of floor, ceiling and side walls not only locally but also globally. In this paper, we propose an effective procedure for LOS-check to solve this difficult situation. Numerical examples are shown for traced rays as well as total link-cost distributions in sinusoidal and cross-type tunnels.